Interim progress analysis of adapted gymnastics practices applied in beginner football training process - Kolunin, E. T. (Theory and Practice of Physical Culture, 2018)
The study analyses benefits of adapted gymnastics practices in the beginner football training process as verified by the footballers` physical fitness rating tests in the period of 2015 to 2017. It should be noted that the children`s physical progress tests showed wavelike progress profiles largely dependent on the individual physical development rates and applied training methods. The adapted gymnastics practices applied in the Experimental Group (EG) of beginner footballers were prudently designed to ensure due body conditioning, health improvement and physical progress in the first training year. In the second training year, the EG trainings included the adapted gymnastics practices designed to simulate football skills, facilitate the football technical skills building and special physical progress. The study data and analyses demonstrated benefits of the adapted gymnastics practices for the beginner football training process designed with due account of the sensitive body development periods, kinesiological potentials and specific game requirements in the physical progress securing training process. The study found close correlations between some efficient gymnastic exercises and progress in special physical fitness tests.